Oksidasi Minyak dalam Emulsi O/W : Mekanisme dan Pengendaliannya - Posman Sibuea; Sri Rahardjo; Umar Santoso; Zuheid Noor (agriTECH, 2004)
Oxidation can alter the flavor and nutritional quality of foods and produces toxic and color compounds, which make foods less acceptable or unacceptable to consumers. Consequently, lipid oxidation has been extensively studied in bulk fats and oils, and there is a fairly good understanding of the mechanisms and the factors that affect oxidation in such systems. On the other hand, lipid oxidation is still not well understood in systems in which the fat is dispersed as emulsion droplets, although a large number of foods exit partially or entirely in the form of emulsions. This article reviews discusses the major factors that influence of the mechanism and controlling lipid oxidation in 0/W (oil-in-water) emulsions.